The Wildcat That Lives in Me: A Review on Free-Roaming Cats (Felis catus) in Brazil, Focusing on Research Priorities, Management, and Their Impacts on Cat Welfare - Gonçalves, Luana S.; de Souza Machado, Daiana; Caçador, Maria Eduarda; Ferreira, Giovanne Ambrosio; Dickman, Christopher R.; Ceballos, Maria Camila; Prezoto, Fabio; Sant’Anna, Aline Cristina [UNESP] (MDPI, 2025)
Domestic cats (Felis catus) currently occupy the 38th place in the Global Invasive Species Database. Free-roaming cats potentially have broad-ranging impacts on wildlife, occupying most terrestrial environments globally as house pets, strays, or feral animals. In Australia, for example, cats are responsible for the decline in many vertebrate populations and extinction of several native mammals. However, in Brazil, few studies have explored either direct impacts of predation on wildlife, or other indirect impacts, such as competition for resources, niche overlap, hybridization, and disease transmission. In this review, we summarize and discuss 34 original research reports, published between 2001 and 2020, on impacts of free-roaming cats in Brazil. We briefly contextualize the history of cat domestication and present that, in Brazil, more studies have focused on the potential of free-roaming cats to transmit disease than to exert impacts via predation or competition on wildlife. More studies were conducted in Brazilian mainland areas (n = 23)—notably in Atlantic Forest—than on islands (n = 11). The review highlights potential impacts of cats on wildlife. We also discuss how control management strategies can affect the welfare of domestic cats, identifying potential knowledge gaps as well as opportunities for future research. Finally, understanding risks of cat predation is necessary to inform future measures to mitigate impacts on wildlife, without neglecting cat welfare.
Keywords: animal welfare; behavior; biodiversity; domestic cats; invasive species